Filsafat Moral: Disequilibrium Citra dan Realita Etika Masyarakat Indonesia (Studi Fenomenologi Penggunaan Media Sosial Instagram) - Ida Bagus Putu Adnyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Initially, the image of the Indonesian nation was that of a humanist, friendly and polite nation. However, as technology advances, Indonesian people begin to put aside the noble values of morality and ethics in everyday life. Conceptually, technology is not the cause of the moral and ethical conditions of the Indonesian people today, but technology has also become a mediator that causes the Indonesian people to override the noble values of morality that are the identity of the Indonesian nation. The purpose of this study is to determine the condition of morality and ethics of the Indonesian people in social life, especially from the aspect of using social media. This research is a qualitative research that uses a phenomenological study approach in studying and analyzing phenomena or events that occur in the field. The data collection method used in this research is through observation of research objects, literature studies, online data searches and using a phenomenological approach as the foundation. The data analysis technique used in this study is the data analysis technique proposed by Miles and Huberman while the data validity test technique in this study was carried out using the credibility test. This study finds that there is a disequilibrium between the image that has been attached to the identity of the Indonesian nation and the reality that occurs in the lives of Indonesian people today. This disequilibrium leads to the degradation of the image of the Indonesian people in the reality of social media, especially Instagram.